Penerapan Strategi Dan Teknik Bermain Dalam Pertandingan Sepak Takraw: Penelitian - Dicky Edwar Daulay; Boby April Judika Gultom; Evelkin Sinaga; Jen Geovani Barus; Joko Wantri Lumbantoruan; Maichel Jhosua; Putri Ayu Nengsi Siagian; Raihan Amin Harahap; Rhidoni Sinaga (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to determine the level of basic technical skills in sepak takraw among athletes from Deli Serdang Regency. The research method used was quantitative descriptive, with a sample of 18 athletes selected using a saturated sampling technique. The research instruments consisted of tests on seven components of basic sepak takraw techniques, namely kicking, thigh control, chest control, shoulder control, heading, smash, and block. The data were analyzed using descriptive statistics to obtain the mean, standard deviation, maximum, and minimum values. The results showed that the basic technical skills of sepak takraw athletes in Deli Serdang Regency were in the “moderate” category, with 27.8% of athletes in the high category, 50% in the moderate category, and 22.2% in the low category. No athletes were found in the very high or very low categories. The conclusion of this study indicates that the athletes’ basic technical skills are fairly good but still need improvement, particularly in smash and block techniques, through more focused and continuous training programs.